Chemokine Receptor 4–Targeted 68Ga-Pentixafor PET/CT in Response Assessment of Waldenström Macroglobulinemia/Lymphoplasmacytic Lymphoma: Comparison to 18F-FDG PET/CT. (September 2021) - Pan, Qingqing; Cao, Xinxin; Luo, Yaping; Li, Jian; Li, Fang
Abstract : Purpose: 68 Ga-pentixafor PET/CT was reported to have a high sensitivity in detecting tumor involvement of Waldenström macroglobulinemia/lymphoplasmacytic lymphoma (WM/LPL) in our previous study. We aimed to further investigate its value in response assessment in WM/LPL. Patients and Methods: Fifteen patients with WM/LPL were recruited in a prospective cohort study and underwent both 68 Ga-pentixafor and 18 F-FDG PET/CT at baseline and posttreatment. PET/CT-based responses were analyzed with visual assessments and compared with clinical response. Results: At baseline, all of the 15 patients had a positive 68 Ga-pentixafor PET/CT scan, whereas 18 F-FDG PET/CT was positive in 11/15 patients. After chemotherapy, the overall response rate was 86.7% (13/15), and 68 Ga-pentixafor PET/CT showed different degree of tumor response from baseline in these patients. In the 2 patients with progressive disease, 68 Ga-pentixafor PET/CT detected new lesions or remarkable increase of 68 Ga-pentixafor uptake in tumor involvements. However, 18 F-FDG PET/CT failed to detect the improvement of disease in 6/13 patients and missed disease progression in 1 of the 2 patients. Conclusions: 68 Ga-pentixafor PET/CT outperformed 18 F-FDG PET/CT in response assessment of WM/LPL.